PHYSICAL TYPOLOGY OF COASTAL AREA IN THE TELUK AMBON DALAM - Yuni Andriyani Safitri; Nurul Khakim; Sri Rum Giyarsih (USN Kolaka, 2021)
The physical typology of the coastal area in this study is built from a combination of landforms, slopes, and materials. The research method used is a field survey to validate land units on secondary maps and GIS analysis to process typology maps of coastal areas based on a process-response system matrix. The results of this study indicate that the TAD coastal area has only one coastal typology, namely the type of land deposition with a gentle slope characteristic, the constituent material in the form of loose material and the terrain which is dominated by alluvial plains. As a result, in general, the coastal area of Teluk Ambon Dalam is easy to develop and manage.